2021
DOI: 10.3390/diagnostics11091640
|View full text |Cite
|
Sign up to set email alerts
|

Laser Doppler Imaging for Treating Vascular Complications from Procedures Involving Dermal Fillers: Case Series and Literature Review

Abstract: Vascular occlusion is a rare but severe complication of dermal filler injections. Early treatment of this complication produces better outcomes. Current diagnostic methods for vascular occlusion in the skin are subjective and imprecise; these include capillary refill time, skin color, and reports of pain. This study aimed to assess the use of laser Doppler imaging (LDI) in the evaluation and treatment of vascular complications caused by dermal filler injections. This retrospective study used laser Doppler imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Firstly, ultrasound has successfully determined that the needle or cannula is positioned in the correct plane and not within or near a vessel [111] . Schelke et al discussed how the use of doppler ultrasound can help distinguish vessels as well as the direction of blood flow [Figure 6] [112] . Rocha et al recommended that once the needle or cannula is determined to be in the correct location, the filler can be injected without aspiration [111] .…”
Section: Mapping Vasculature To Prevent Intravascular Filler Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, ultrasound has successfully determined that the needle or cannula is positioned in the correct plane and not within or near a vessel [111] . Schelke et al discussed how the use of doppler ultrasound can help distinguish vessels as well as the direction of blood flow [Figure 6] [112] . Rocha et al recommended that once the needle or cannula is determined to be in the correct location, the filler can be injected without aspiration [111] .…”
Section: Mapping Vasculature To Prevent Intravascular Filler Injectionmentioning
confidence: 99%
“…Doppler ultrasound may be able to be used to detect the lack of perfusion, and in rare cases, an ischemic vessel may be able to be injected with hyaluronidase under ultrasound guidance. Schelke et al reported on a case of how, upon crusting under the lip after upper lip augmentation, 150 U of hyaluronidase was injected with ultrasound guidance [112] . A case in which ultrasound was used to inject hyaluronidase into a visualized filler deposit is seen in Figure 8.…”
Section: Diagnosing Areas Of Ischemia From Filler Complicationsmentioning
confidence: 99%